Differentiation Between Dementia With Lewy Bodies And Alzheimer’s Disease Using Voxel-Based Morphometry Of Structural MRI: A Multicenter Study - Matsuda H (Dove Medical Press, 2019)
Hiroshi Matsuda,1 Kota Yokoyama,2 Noriko Sato,2 Kengo Ito,3 Kiyotaka Nemoto,4 Hiroshi Oba,5 Haruo Hanyu,6 Hidekazu Kanetaka,6 Sunao Mizumura,7 Shin Kitamura,8 Hitoshi Shinotoh,9 Hitoshi Shimada,9 Tetsuya Suhara,9 Hitoshi Terada,10 Tomoya Nakatsuka,10 Shinobu Kawakatsu,11 Hiroshi Hayashi,12 Takashi Asada,13 Tetsutaro Ono,14 Tomoaki Goto,14 Keiko Shigemori14 1Integrative Brain Imaging Center, National Center of Neurology and Psychiatry, Kodaira, Tokyo, Japan; 2Department of Radiology, National Center Hospital of Neurology and Psychiatry, Kodaira, Tokyo, Japan; 3Innovation Center for Clinical Research, National Center for Geriatrics and Gerontology, Obu, Japan; 4Department of Psychiatry, Faculty of Medicine, University of Tsukuba Hospital, Tsukuba, Japan; 5Department of Radiology, Teikyo University Hospital, Itabashi-ku, Tokyo, Japan; 6Department of Geriatric Medicine, Tokyo Medical University Hospital, Shinjuku-ku, Tokyo, Japan; 7Department of Radiology, Toho University Omori Medical Center, Oota-ku, Tokyo, Japan; 8Department of Internal Medicine, Nippon Medical School Musashi Kosugi Hospital, Kawasaki, Japan; 9Department of Functional Brain Imaging Research, Clinical Research Cluster, National Institute of Radiological Sciences, National Institutes for Quantum and Radiological Science and Technology, Chiba, Japan; 10Department of Radiology, Toho University Sakura Medical Center, Sakura, Japan; 11Department of Neuropsychiatry, Aizu Medical Center, Fukushima Medical University, Aizuwakamatsu, Japan; 12Department of Psychiatry, Yamagata University School of Medicine, Yamagata, Japan; 13Section of Psychiatry and Behavioral Sciences, Tokyo Medical and Dental University Graduate School, Bunkyo-ku, Tokyo, Japan; 142nd Group, 2nd Planning Department, 1st Integrated Communication Division, Communication and Information Center, Information Innovation Operations, Dai Nippon Printing Co., Ltd., Tokyo, JapanCorrespondence: Hiroshi MatsudaIntegrative Brain Imaging Center, National Center of Neurology and Psychiatry, 4-1-1, Ogawahigashi, Kodaira, Tokyo 187-8551, JapanTel +81 42 341 2711Email matsudah@ncnp.go.jpBackground: The differential diagnosis of dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD) is particularly important because DLB patients respond better to cholinesterase inhibitors but sometimes exhibit sensitivity to neuroleptics, which may cause worsening of clinical status. Antemortem voxel-based morphometry (VBM) using structural MRI has previously revealed that patients with DLB have normal hippocampal volume, but atrophy in the dorsal mesopontine area.Objectives: The aim of this multicenter study was to determine whether VBM of the brain stem in addition to that of medial temporal lobe structures improves the differential diagnosis of AD and DLB.Methods: We retrospectively chose 624 patients who were clinically diagnosed with either DLB (239 patients) or AD (385 patients) from 10 institutes using different MR scanners with different magnetic field strengths. In all cases, VBM was performed on 3D T1-weighted images. The degree of local atrophy was calculated using Z-score by comparison with a database of normal volumes of interest (VOIs) in medial temporal lobe (MTL) and the dorsal brain stem (DBS). The discrimination of DLB and AD was evaluated using Z-score values in these two VOIs. MRI data from 414 patients were used as the training data set to determine the classification criteria, with the MRI data from the remaining 210 patients used as the test data set.Results: The DLB and AD patients did not differ with respect to mean age or Mini-Mental State Examination scores. Z-index scores showed that there was significantly more atrophy in MTL of AD patients, compared to DLB patients and in DBS of DLB patients, compared to AD patients. The discrimination accuracies of VBM were 63.3% in the test data set and 73.4% in the training data set.Conclusion: VBM of DBS in addition to that of MTL improves the differentiation of DLB and AD.Keywords: dementia with Lewy bodies, Alzheimer’s disease, MRI, voxel-based morphometry